Opening the Trinity: developing the "open theism" debate - D. T. Williams (Acta Theologica)
The reconciliation of the omniscience of God with the free choices of humanity is a problem which has taxed Christian thinkers for centuries. Recently the issue has become prominent with the emergence of support for "open theism", the belief that free will is such that God cannot know the future, simply because it has not yet happened. This idea has produced considerable opposition largely based on the perceived insecurity with which it leaves Christians, and the feeling that it diminishes God. A further solution to the problem can be based on the concept of God's kenosis, that God has freely chosen to limit himself, specifically his knowledge. As this is a freely chosen action of God, so not an inherent limitation, and is temporary, it meets the fundamental objections to open theism. At the same time kenosis was done for the sake of enabling a relationship with God, in which Christians do find ultimate security.